(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
The use of firearms is increasing in our society, which increases the incidence of gunshot injuries in developing countries like India. Atypical firearm injuries are uncommon where they present as other injuries, different numbers of entry and exit wounds. The appearance of gunshot entrance wounds on the body depends upon many factors including, the type of firearm, the type of ammunition, the location of the wound on the body, and the circumstances of how a wound was sustained. Atypical gunshot entrance wounds may be created when the bullet is destabilized prior to entering the body and consequently does not enter the body nose first but sideways or at an angle. The most common causes of an atypical entrance wound are bullet ricochet and interaction with an intermediate target. In ordinary circumstances in rifled firearm; number of entry wounds should match exit wounds and when they don’t match, it indicates presence of bullet inside the body. One such atypical case of firearm injuries was brought to NCH Surat for PM examination. There were three firearm injuries on the body, out of which one is entry and two is exit wound.